1987
DOI: 10.1677/joe.0.1120027
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nutrition and immunization against somatostatin on growth and insulin-like growth factors in sheep

Abstract: The effect of immunizing against somatostatin (SRIF), with SRIF conjugated to bovine thyroglobulin, was examined in cross-bred sheep fed either cut pasture or lucerne pellets. Plasma concentrations of GH were unaffected by SRIF immunization, but were lower in pellet-fed sheep. Plasma concentrations of insulin-like growth factor I (IGF-I) increased after immunization in sheep on both diets. Pasture-fed sheep had lower plasma concentrations of IGF-I than those on pellets. Sheep showed a small increase in growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 14 publications
4
18
1
Order By: Relevance
“…In their recent review of published data on the effects of SRIF-immunization in cattle, noted that there was evidence for increased fat deposition in other studies too. Examination of the data of Bass et al (1987) suggests there may be a nutrition X immunization interaction with regard to this effect, as only immunized sheep on a good quality pelleted diet of lucerne and barley showed any evidence of increased carcass fat, while those on cut pasture had similar carcass composition to those of control animals. reported significant proportional increases of 0-26 and 0-35 in perirenal and mesenteric fat depot weights respectively in SRIF-immunized bulls compared with non-immunized controls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In their recent review of published data on the effects of SRIF-immunization in cattle, noted that there was evidence for increased fat deposition in other studies too. Examination of the data of Bass et al (1987) suggests there may be a nutrition X immunization interaction with regard to this effect, as only immunized sheep on a good quality pelleted diet of lucerne and barley showed any evidence of increased carcass fat, while those on cut pasture had similar carcass composition to those of control animals. reported significant proportional increases of 0-26 and 0-35 in perirenal and mesenteric fat depot weights respectively in SRIF-immunized bulls compared with non-immunized controls.…”
Section: Discussionmentioning
confidence: 99%
“…The anabolic effects of GH are believed to be mediated by IGF-1 so it is perhaps not surprising that a more consistently observed response to SRIF immunoneutralization is an increase in plasma IGF-1 concentrations (e.g. Bass et al, 1987), presumably mediated via GH. However plane of nutrition is known to affect the GH-IGF-1 axis (Breier et al, 1988) and this is likely to also be important in achieving both an IGF-1 response and a growth response to immunization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Varner et al (1980) observed higher GH concentrations but a reduced growth rate in SRIF-IMM animals. Others have reported increases in daily gain and IGI-I levels, but no change in GH concentrations (Spencer et al, 1983a;Laarveld et al, 1986), whereas Bass et al (1987) reported increased IGF-1 with no effect on GH and a slight increase in growth rate. Nevertheless, when summarizing data taken from the literature, , using meta-analysis on weighted group averages from several studies, showed that daily gain and feed intake were increased by 11.4 and 4.2%, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…In sheep, Varner et al (1980) observed higher GH concentrations in SRIF immunized (SRIF-IMM) cattle, but a reduced growth rate, whereas others have reported increases in daily gain but no change in GH concentrations (Spencer et al, 1983a;Laarveld et al, 1986;Bass et al, 1987). Sun et al (1990) reported increases in live weight gain, N retention and apparent digestibility of DM and N in SRIF-IMM lambs.…”
Section: Introductionmentioning
confidence: 96%